BET405 – Medical and Veterinary Helminthology (Helmintologi Perubatan dan Veterinar) July/August 2023 - Pusat Pengajian Sains Kajihayat, PPSK (Universiti Sains Malaysia, 2023)
Second Semester Examination 2022/2023 Academic Session July/August 2023 BET405 – Medical and Veterinary Helminthology (Helmintologi Perubatan dan Veterinar) Duration : 2 hours (Masa : 2 jam)